2012
DOI: 10.1080/02673037.2013.729265
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Housing Market Conditions on Residential Property Upkeep

Abstract: This paper assesses the impact of housing market conditions on the theoretically motivated and empirically observed negative relationship between loan to value ratios and home maintenance expenditures. If the relationship is causal, then a down housing market will result in significantly decreased upkeep in the housing stock. The large rise and fall in home prices during the 2001-2009 period allows a unique opportunity to analyze the response of homeowners to changing housing market conditions. Data from the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The negative externality can happen before the official declaration of foreclosure because homeowners at high risk of default are less financially capable and poorly incentivized to allocate resources towards home maintenance (Harding et al, 2000). Examining American Housing Survey data from the 2007 financial recession, Leonard (2013) found that homeowners at very high foreclosure risk reported lower routine maintenance expenditures while still occupying their home. During the foreclosure process, properties may be vacant for some time-further attracting vandalism and crime, which may exacerbate the blight.…”
Section: Hypothesismentioning
confidence: 99%
“…The negative externality can happen before the official declaration of foreclosure because homeowners at high risk of default are less financially capable and poorly incentivized to allocate resources towards home maintenance (Harding et al, 2000). Examining American Housing Survey data from the 2007 financial recession, Leonard (2013) found that homeowners at very high foreclosure risk reported lower routine maintenance expenditures while still occupying their home. During the foreclosure process, properties may be vacant for some time-further attracting vandalism and crime, which may exacerbate the blight.…”
Section: Hypothesismentioning
confidence: 99%
“…However, evidence suggests that the majority of U.S. homeowners actually increased routine maintenance expenditures on their homes during the financial recession. The exception were homeowners with very low income and very low home equity (Leonard 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence suggests that the majority of U.S. homeowners actually increased routine maintenance expenditures on their homes during the financial recession. The exceptions were homeowners with very low income and very low home equity (Leonard 2013). Thus, it is possible that the estimated impact of high poverty neighborhoods on the probability of resolution of the foreclosure process might be upward biased to the extent low household income is correlated with declines in routine home maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted on young people’s housing preferences and behaviours; their support expectations from parents in home-buying (Wong, 2017), how this support mechanism is related to parents’ course of life and housing career (Albertini et al , 2018), the effects of differences between generations (Stebbing and Spies-Butcher, 2016), the effects of the features of housing market and housing policies (Leonard (2013; Visser et al , 2013; Walter et al , 2015), the effects of education debts during and after studentship (Andrew, 2010), perception of shared housing and shared living (Bricocoli and Sabatinelli, 2016), the role of social norms and family relations (Lux et al , 2017), drawbacks in accessing social assistance mechanisms are seen to be examined (McKee, 2012). The first result that calls attention among overall results of these studies is the significant fall of the ratio for Generation Y to own a house compared to the previous generation.…”
Section: Literature Reviewmentioning
confidence: 99%